Concurrent Force Feedback on Load Symmetry in Total Knee Arthroplasty Patients - Steni Sackiriyas; Becky Heinert; Drew Rutherford; Gwen M Fritz; Thomas W Kernozek (International Journal of Sports Physical Therapy)
# Background and Purpose